Niue in New Zealand Legislation - Angelo, Tony; Perham, Elisabeth; Lau, Yi-Shen (Victoria University of Wellington Law Review, 2021)
This article provides guidance to non-Niuean lawyers, and particularly for New Zealand lawyers, who want to ascertain the Niue law on a particular matter. The need arises because a New Zealand statute that was extended to be part of the law of Niue may still be in force in New Zealand and in Niue but, because of the passage of time and legislative action in one or both of the countries, the text and effect of the statute may be different in each country.